A review of pharmacokinetic and pharmacological properties of asiaticoside, a major active constituent of Centella asiatica (L.) Urb. (10th February 2023) - He, Ziliang; Hu, Yeye; Niu, Zhiqiang; Zhong, Kang; Liu, Tingwu; Yang, Meng; Ji, Lilian; Hu, Weicheng
Abstract: Ethnopharmacological relevance: Centella asiatica (L.) Urb., a potential medicinal plant, is widely used in orient traditional medicine. Its major active constituents include asiaticoside (AS), madecassoside (MS), asiatic acid and madecassic acid. Thereinto, AS is a pentacyclic triterpenoid saponin with a variety of pharmacological effects including antitumor, neuroprotective and wound healing effects. Aim of the study: In this review, we summarize the pharmacokinetics, safety and pharmacological properties of AS. Materials and methods: We gathered information about AS from articles published up to 2022 and listed in Google scholar, PubMed, Web of Science, Elsevier, and similar databases. The keywords used in our search included "asiaticoside", " Centella asiatica ", "pharmacokinetics", "nerve", "cancer", "skin", etc. Results: AS appeared to degrade through a first-order reaction and had low biotoxicity. However, the pharmacokinetic properties of AS differed according to species. AS is highly blood-brain-barrier permeable without any harmful side effect. It has a variety of pharmacological effects including anti-neural inflammation and anti-cancer properties, as well as protective properties for the skin, cardiovascular system, and pulmonary system. Conclusion: This review comprehensively summarized current information regarding the pharmacokinetic and pharmacological properties of AS, and supported the pharmaceutical value of this compound. Future research should focus on improving bioavailability of AS and conducting clinical assessment. Graphical abstract: Image 1 Highlights: Asiaticoside (AS) is the main component of Centella asiatica. The comprehensive pharmacological activities of AS were summarized. The pharmacokinetics and safety of AS was discussed. Future investigation should focus on improving bioavailability of AS.